EFEKTIFITAS PEMBERIAN NAFKAH TERHADAP ANAK YANG BELUM DEWASA PASCA TERJADINYA PERCERAIAN - Pramana, Dian; Rahmayani, Nuzul; Andriaman, Mahlil (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Abstract: The purpose of this research is to see how the effectiveness of providing income to immature children post-divorce at the Bukittinggi City Religious Court aims to protect and guarantee the rights of immature children after the divorce is still fulfilled. The method used in this study is an empirical juridical method or empirical data collection, which uses primary data or data sourced directly from the field obtained through interviews and matches it with legal materials regarding events found in the field or secondary data, which still requires further processing. Carry on. The study results show that post-divorce support for immature children has yet to work well or effectively. The causes are economic factors, and the mother can provide for her child, the father/ex-husband is no longer in the same area as the child, poor communication between the ex-husband and ex-wife, and the ex-husband remarried. Therefore, a legal remedy can be taken by the ex-wife, namely by applying to the execution of collateral confiscation of the ex-husband's assets which does not kill his livelihood based on SEMA No. 5 of 2021.Keywords : Effectiveness; Divorce; Livelihood of Children who are Not yet dult.